La banquette antiérosive fruitière dans le moyen atlas marocain : le projet Khénifra - Régis Peltier; Mohamed Sabir; Charles Lilin; Anaïs Oddi; Frank Schneider; Florence Amia; Daniel Kübler; Thea-Katharina Wiesinger; Armand-Yvon Mengome-Ango (VertigO)
Fruit arboriculture terrace consists of digging ditches of approximately 50 cm in both width and depth, in contour lines, at the bottom of which fruit trees are planted. It has been used by the Project for Participative Development in the Central Middle Atlas region, which duly planted 97,000 m of them over a 212 ha area, between 2005 and 2007.In 2007, a survey was carried out with the cooperation of 16 farmers of this region to determine how they perceived the technique and what improvements or alternatives they might be able to suggest. The surveys were combined with and equal number of on site visits and numerous interviews with key resource persons. All the farmers attach great importance to fruit trees who give them higher income that the breeding of sheep and the planting of cereal crops. It’s why they accept the project’s terrace digging and fruit planting in their fields. Yet few were convinced of the erosion control effect of the terraces, rather oversensitive to heavy rainfall and cattle trampling, especially in steep slopes. When they carried out the work themselves, certain farmers demonstrated a preference for surrounding the trees by a shallow crescent-shaped ditch, whose dyke was reinforced by a wall made from dried stones. In this way they could be set out right along the entire length of the irrigation ditches in a slight slope. The advisory package developed by this project, was well accepted because of its virtual absence of cost, and despite the drawbacks and dangers of the erosion control technique. In terms of project approach, it remains an open question as to whether or not it might have been better to distance oneself from the feedback given in relation to both erosion and fruit arboriculture.